The Impact of Climate Shocks on Conflicts in Laikipia County, Kenya (National Security: A Journal of the National Defence University-Kenya, 2025)
This research interrogates how climate shocks (droughts, floods, and heatwaves, among others) affect the level of conflict in Laikipia County. The Environmental Scarcity Theory (EST) served as the theoretical foundation of this study. The research employed a mixed-methods approach, combining qualitative and quantitative research methods to achieve its aims. The study was conducted in Laikipia County, using purposive and stratified sampling techniques to obtain a sample of 150 respondents from a target population comprising the Laikipia County Climate Change Committee, the Ministry of Interior and National Administration, the State Department of ASALs and Regional Development officials, residents, academic personnel, local police officers, area chiefs, and traditional leaders. One hundred thirty-eight respondents completed the survey, yielding a response rate of 92%. Consequently, primary data were collected through 21 key informant interviews (KIIs) and 117 questionnaires. The quantitative data was analysed by computing descriptive statistics, which were presented in tables and graphs. Conversely, qualitative data was analysed using thematic analysis and presented in narrative form. Additionally, secondary data came from various relevant sources, including books, academic journals, government reports, and online materials. The study established that Laikipia County experiences increased conflicts due to climate shocks that create a scarcity of resources (land, pasture, and water), as well as disruptions to livelihoods and forced population movements. This study concludes that climate shocks have increased the frequency and intensity of conflicts experienced in Laikipia County. To address this scenario, a multi-pronged trajectory is recommended as the solution to climate-induced disputes in the area of study.
Keywords: Climate shocks, environmental scarcity, conflict, Arid and Semi-Arid Lands (ASALs), Laikipia County